2021
DOI: 10.1007/s10067-021-05949-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of dual energy computed tomography in the differentiation of acute gout flares and acute calcium pyrophosphate crystal arthritis

Abstract: Objectives To analyse the diagnostic impact of dual energy computed tomography (DECT) in acute gout flares and acute calcium pyrophosphate (CPP) crystal arthritis when compared to the gold standard of arthrocentesis with compensated polarised light microscopy. Microscopy results were also compared to musculoskeletal ultrasound (MUS), conventional radiographs, and the suspected clinical diagnosis (SCD). Methods Thirty-six patients with a suspected gout flar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
(48 reference statements)
0
14
0
1
Order By: Relevance
“…Among studies assessing the diagnostic capacity of DECT for the diagnosis of gout, 21/28 (75%)6 18 19 21–38 and 21/28 (75%)6 18 19 21–24 26 29–31 33–36 38–43 reported sensitivity and specificity, respectively of ≥80%. The sensitivity ranged from 52.8% to 100.0%, the specificity from 50.0% to 100.0%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among studies assessing the diagnostic capacity of DECT for the diagnosis of gout, 21/28 (75%)6 18 19 21–38 and 21/28 (75%)6 18 19 21–24 26 29–31 33–36 38–43 reported sensitivity and specificity, respectively of ≥80%. The sensitivity ranged from 52.8% to 100.0%, the specificity from 50.0% to 100.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Three out of these five studies (60%)6 38 41 found numerically lower sensitivity (35.7% vs 92.9%, 38.0% vs 77.6% and 55% vs 81%) with similar specificity in the group with shorter disease duration of 1 year or less while two studies (40%)31 44 found no difference between the subgroup with a shorter disease duration and the overall cohort. In 16/28 (57.1%) studies performing DECT, only the (previously) symptomatic side was assessed,18 19 22 26–28 33 37–41 43–46 in 5/28 (17.9%) studies, a predefined set of joints was assessed21 24 25 29 34 and in the remaining 1/28 study (3.6%), the (most) symptomatic joint or recently symptomatic joint as well as the contralateral metatarsophalangeal one joint was assessed 42. The remaining studies23 30–32 35 47 were meta-analyses without data on the assessed joints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of tophi on imaging suggests gouty arthropathy rather than an infectious or inflammatory arthropathy. Imaging, particularly DECT, can help differentiate acute calcium pyrophosphate arthropathy from gouty arthropathy, although a recent study showed that DECT may have a lower sensitivity for acute gout flares than previously described, and that DECT sensitivity for acute calcium pyrophosphate crystal arthritis is lower than that of US [ 60 ].…”
Section: Clinicalmentioning
confidence: 99%
“…Diese Methode erlaubt eine Abgrenzung von Natriumurat-Kristallen gegenüber ihrer Umgebung in der CT-Bildgebung und eine farbkodierte Darstellung zur Befundung (▶ Abb. 5)[7]. Die konventionelle Röntgenaufnahme als weiteres bildgebendes Verfahren präsentiert sich im akuten Gichtanfall meist unauffällig und kommt in erster Linie zur Differenzialdiagnostik oder bei chronischer Gicht zur Darstellung von Gelenkerosionen oder röntgendichter Uratablagerungen (Tophi) infrage.Sofern dem Patienten (z.…”
unclassified